PENGARUH PEMBERIAN NUGGET REMIS SEBAGAI MAKANAN TAMBAHAN TERHADAP PENINGKATAN BERAT BADAN BALITA GIZI KURANG - Ratna Dewi; Armita Sri Azhar; Maya Fernanda Dielsa; Welly Handayani; Try Maya Syafputri; M. Saka Abeiasa (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
According to the World Health Organization (WHO) in 2020, the global prevalence of undernourished toddlers experiencing wasting reached 45.4 million children (8%). One of the major nutritional problems in Indonesia is undernutrition among children. This study aimed to determine the effect of supplementary feeding with clam nugget products on weight gain among undernourished toddlers. This study employed a quantitative research design using a one-group pretest-posttest approach. The population consisted of all undernourished toddlers in the working area of the Ketaping Community Health Center, Padang Pariaman Regency totaling 37 children. The sampling technique used was purposive sampling, resulting in 34 respondents. The study was conducted in April 2025 in the in the working area of the Ketaping Community Health Center, Padang Pariaman RegencyData analysis was performed using the dependent test. The results showed that the mean body weight of toddlers before (pretest) receiving the supplementary food “Clam Nuggets” was 11.829 kg, with a standard deviation of 1.8320 and a standard error of 0.3142. After (posttest) receiving the supplementary food “Clam Nuggets,” the mean body weight increased to 12.079 kg, with a standard deviation of 1.234 and a standard error of 0.3110. Statistical analysis showed a p-value of 0.000 (P 0.05). The study concluded that supplementary feeding with clam nuggets had a significant effect on increasing body weight among undernourished toddlers. The researchers suggest that this intervention can be understood and applied in daily midwifery practice as a non-pharmacological treatment to improve toddlers’ body weight, as it is safe, free from side effects, and easily accessible. Keywords: Clam Nugget Supplementary Feeding, Body Weight, and Nutritional Status